Global Financial Conditions and Monetary Policy Autonomy - Caceres, Carlos (IMF Working Papers; Working Paper ;, 2016)
Is the Mundell-Fleming trilemma alive and well? International co-movement of asset prices takes place alongside synchronized business cycles, complicating the identification of financial spillovers and assessments of monetary policy autonomy. A benchmark for interest rate comovement is to impose the null hypothesis that central banks respond only to the outlook for domestic inflation and output. We show that common approaches used to estimate interest rate spillovers tend to understate the degree of monetary autonomy enjoyed by small open economies with flexible exchange rates. We propose an empirical strategy that partials out those spillovers that are associated with impaired monetary autonomy. Using this approach, we revisit the predictions of the trilemma and find more compelling evidence that flexible exchange rates deliver monetary autonomy than prior work has suggested.